Design of a wideband quasi‐Yagi antenna with filtering response - Yanyuan Zhu (Wiley, 2021)
Abstract This letter presents a wideband quasi‐Yagi antenna with high selective filtering responses and good radiation performance. The proposed antenna is formed by a microstrip‐slotline‐microstrip transition structure as the filtering network, a driver dipole, and a parasitic strip element. Attributing to the integrated wideband filtering balun network, a wideband performance in the antenna with stable gain can be achieved. Moreover, two radiation nulls are introduced near both sides of the gain passband by utilizing the source‐load coupling in the filtering network to acquire a sharp skirt selectivity. To verify the design concept, a prototype is fabricated and measured. Results exhibit an impedance bandwidth of 63.5% from 3.0 to 5.79 GHz with a stable gain average of 5 dBi over the whole operation band. Besides, two radiation nulls occur at 2.6 and 6.85 GHz, respectively. The simulated results are in good agreement with the measured counterparts.